2009
DOI: 10.1155/2009/180643
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Sonographic Diagnosis of Pharyngeal Teratoma: Our Experience of a Rare Case with Review of the Literature

Abstract: Background. Teratomas are the most common tumors. They are usually localized in the sacrococcygeal area, while the pharyngeal localization is very rare. The number of cases of stomatopharyngeal teratomas detected prenatally via sonography is very small. Case Report. We present the case of a 24-year-old primipara at 18 weeks' gestation, that at the routine ultrasound scan, the fetus was found with an echogenic mass, filling the stomatopharyngeal cavity and protruding from the mouth. Other abnormalities were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Mature teratomas are benign and they do not Türk Ped Arş 2014; 49: 257-60 Bayır et al Nasopharyngeal mature teratoma in the newborn lead to invasion or metastasis in the surrounding tissues. Mature teratomas may contain hair, sweat gland, adipose gland, tooth, nail, nerve, muscle, cartilage, bone and adipose tissues originating from the three germ layers, samples of organs including exocrine glands, liver, pancreas and thyroid and respiratory tract and gastrointestinal tract epithelium (7,8). The histopathological examination of our case revealed tooth, adipose tissue, mature cartilage and glandular and glial tissues.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Mature teratomas are benign and they do not Türk Ped Arş 2014; 49: 257-60 Bayır et al Nasopharyngeal mature teratoma in the newborn lead to invasion or metastasis in the surrounding tissues. Mature teratomas may contain hair, sweat gland, adipose gland, tooth, nail, nerve, muscle, cartilage, bone and adipose tissues originating from the three germ layers, samples of organs including exocrine glands, liver, pancreas and thyroid and respiratory tract and gastrointestinal tract epithelium (7,8). The histopathological examination of our case revealed tooth, adipose tissue, mature cartilage and glandular and glial tissues.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that teratomas may develop as a result of development of embrionic germ cells in these areas. According to another assumption, it has been reported that embrionic cells other than germ cells have all genetic codes and teratomas may also develop from these cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…В большинстве наблюдений тератомы представлены различ-ными объемами эпидермиса, придатков кожи, гладких мышц, а также эпителия дыхательных путей и желудочно-кишечного тракта [33]. Мо-гут встречаться элементы хрящей, костей, лим-фоидной ткани, поджелудочной железы, щито-видной железы, печени [34,35]. В ряде случаев отмечалось наличие эмбриональной ткани, пре-имущественно незрелой нейроэктодермы с примитивными медуллобластоподобными клет-ками и зачатки сетчатки [36].…”
Section: заключениеunclassified
“…Teratomas are the most common perinatal tumours developed from multipotent stem cells, are usually extragonadal and contain tissues of ectodermal, endodermal and mesodermal origin, foreign to the anatomic site, in which they arise [1][2][3] . Teratomas account for 25%-52% of all congenital tumours and have a yearly incidence of one in 20 000 to one in 40 000 live births 3,[4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Teratomas account for 25%-52% of all congenital tumours and have a yearly incidence of one in 20 000 to one in 40 000 live births 3,[4][5][6][7] . Sacrococcygeal teratomas have an incidence of 35 000-40 000 live births and have usually a female predominance [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%